Novel modified frailty index predicts completion of adjuvant chemotherapy in resectable pancreatic cancer in a dual center study - Naotake Funamizu; Shozo Mori; Akimasa Sakamoto; Masahiko Honjo; Kei Tamura; Katsunori Sakamoto; Kohei Ogawa; Yuzo Umeda; Taku Aoki; Yasutsugu Takada (Scientific Reports)
Abstract This study demonstrates that the modified frailty index-6 (mFI-6) is a useful tool for predicting the completion of S-1 adjuvant chemotherapy (AC) and associated adverse events (AEs) in patients with pancreatic cancer (PC). mFI-6 is an index that incorporates serum albumin levels into the existing mFI-5, enabling the assessment of patients’ ability to complete S-1 therapy and their risk of developing AEs. This study retrospectively analyzed PC patients from two university hospitals between August 2013 and July 2022. Patients from one hospital were assigned to the testing dataset, while those from the other hospital were used as the validation dataset. Patients were classified as frail if they met at least two of the six criteria, including a serum albumin level of < 3.5 g/dL. In the testing cohort (n = 86 PC patients), frailty patients exhibited greater difficulty in completing S-1 therapy compared to non-frail patients, with a significantly lower completion rate (p = 0.003). Additionally, frail patients demonstrated significantly shorter recurrence-free survival (RFS) and overall survival (OS) compared to their non-frail counterparts. The findings were further validated in the validation dataset, where frail patients exhibited a lower S-1 completion rate and significantly shorter RFS (p = 0.023) and overall survival (OS) (p = 0.045). These results suggest that mFI-6 may be an effective tool for postoperative frailty screening, allowing healthcare professionals to assess patients’ tolerance to S-1 therapy and adjust treatment plans accordingly. Ultimately, the implementation of this index may contribute to improving clinical outcomes for patients with PC.